Environmental, Social, and Governance (ESG) Performance Evaluation to Reduce Potential Greenwashing Based on Sustainable Fitch Index - Gunawan, Juniati; Gunawan, Irene; Liu, Ying Chieh (International Journal of Entrepreneurship and Sustainability Studies, 2023)
Increasing company awareness of environment, social, and governance (ESG) issues is getting more important in relation to financial performances. Investors and other stakeholders require ESG-related information to help them making decisions, in particular investment decisions. This study employed the Sustainable Fitch index to assess the ESG performance, by examining Company G as a case study as this company is considered the first company in Indonesia which went through Sustainable Fitch index evaluation. Sustainable Fitch index was chosen as this index is considered the most related ESG index for companies who would like to publish sustainability bonds and it has a unique methodology. The findings suggest that any companies conducting a Sustainable Fitch ESG assessment should calculate scope 3 emissions and clarify the emission reduction target timeline, including target verification with respect to the United Nations' Science-Based Target (SBT) or net zero targets. These measurements are considered as part of environmental accounting, an emerging accounting issues, related to sustainability. Besides, social performances are also crucial, and one of them is improving the number of women in management positions at all levels.